Avoidable factors associated with pregnant and postpartum patients admitted to two intensive care units in South Africa - Nnabuike Ngene; Jagidesa Moodley; Richard von Rahden; Fathima Paruk; Polycarpe Makinga (South African Medical Association, 2016)
Background. Identification and prevention of any avoidable factor (AVF) associated with pregnancy may reduce critical illnesses and theneed for intensive care unit (ICU) admission.Objectives. To determine AVFs that occurred prior to the admission of pregnant and postpartum patients to two ICUs in South Africa(SA) and the resulting maternal outcomes.Methods. The hospital records of all pregnant and postpartum patients in two public hospital ICUs in Pietermaritzburg, SA, between 1 July2010 and 30 April 2011 were assessed to identify pre-ICU AVFs. Each patient was followed up until the 7th day after ICU discharge or untilhospital discharge (whichever came first), to observe maternal outcomes: survival, death or hypoxic ischaemic brain injury (HIBI).Results. Of 84 patients assessed, 41 (48.8%) had â‰¥1 AVF. Patient-related, administrative and health-worker-related AVFs wereidentified in 32.1% (27/84), 19.0% (16/84) and 7.1% (6/84) of patients, respectively. The most common patient-related AVF was thecommencement of antenatal care after 20 weeksâ€™ gestation. Unavailability of ICU beds was the most common administrative AVF.Iatrogenic pulmonary oedema associated with intravenous fluid resuscitation was the most frequent health-worker-related AVF. Ofwomen who had AVFs, 9 (22.0%) died, 2 (4.9%) had HIBI and 30 (73.2%) suurvived. The relative risk of death or HIBI among patientswith AVF/s was 1.2 (p=0.7).Conclusions. The principal interventions that may prevent AVFs are ongoing community health promotion, strengthening of obstetricskills training on fluid resuscitation and expansion of critical care services.